Rola podniebienia miękkiego w procesie rozwoju techniki wokalnej - Danel, Renata (Logopedia Silesiana, 2014)
What makes human voice unique among other instruments is the fact, that it is a live instrument which, as the only one, produces articulated tones. Among every all articulated organs which are responsible for that phenomenon velum draws the highest attention. It is the moving and articulating organ situated in the oral cavity. Good condition of the organ provides better articulation and resonance, elimination of rhinolalia and development of diapason for the vocalist. These elements are the quintessence of vocal technique. Belittling Underestimating velum’s efficiency leads to many irregularities and faults excluding proper voice projection in the above named aspects.